Kegiatan penyuluhan pencegahan stunting dan pemanfaatan lahan pekarangan (BUNZIKA SEHAT) - Sari, Dina Amilia; Rembulan , Shafa Annisa; Fadilasari , Dewi (JOURNAL of Public Health Concerns, 2025)
Background: Stunting remains a chronic nutritional problem in Indonesia, particularly in rural areas, impacting children's physical growth, cognitive development, and future productivity. According to the 2024 National Child Health Survey (SSGI), the prevalence of stunting in Indonesia reached 19.8%, still above the WHO threshold of 20%. One strategy for preventing stunting is utilizing home gardens as a source of nutritious food. Purpose: To determine the implementation of the BUNZIKA SEHAT outreach program in improving community knowledge and skills in utilizing home gardens as a stunting prevention effort. Method: The activity was conducted in Padang Ratu Village, Wonosobo District. Nineteen participants participated, consisting of housewives and integrated health post (Posyandu) cadres in Padang Ratu Village, Wonosobo District. The selection of participants focused on families with toddlers or those at risk of malnutrition. Interventions were conducted through outreach, training, and mentoring. Results: The implementation showed an increase in participant knowledge, from 89.5% in the good category in the pre-test to 100% in the post-test. The interactive lecture, discussion, and hands-on practice methods proved effective in improving community understanding and skills. Conclusion: The BUNZIKA SEHAT program successfully increased community knowledge and skills in utilizing home gardens, promoted family food security, and can be used as a model for community empowerment to sustainably prevent stunting. Suggestion: The BUNZIKA SEHAT program can be used as a model for community empowerment in a broader area and can be implemented sustainably. Village governments are also expected to provide support by providing seeds, fertilizer, and regular mentoring to ensure program sustainability. Keywords: Balanced nutrition; Community empowerment; Home gardens; Stunting Pendahuluan: Stunting masih menjadi masalah gizi kronis di Indonesia, terutama di wiayah pedesaan, yang berdampak pada pertumbuhan fisik, perkembangan kognitif, dan produktivitas anak di masa depan. Berdasarkan SSGI (2024) prevalensi stunting di Indonesia mencapau 19.8%, masih di atas ambang batas masalah kesehatan menurut WHO sebesar 20%. Salah satu strategi pencegahan stunting aalah melalui pemanfaatan pekarangan rumah sebagai sumber pangan bergizi. Tujuan: Untuk mengetahui implementasi penyuluhan BUNZIKA SEHAT dalam meningkatkan pengetahuan dan keterampilan masyarakat dalam pemanfaatan pekarangan rumah sebagai upaya pencegahan stunting. Metode: Kegiatan dilaksanakan di Pekon Padang Ratu, Kecamatan Wonosobo. Peserta dalam kegiatan ini adalah 19 orang, yang terdiri dari ibu rumah tangga dan kader posyandu di Pekon Padang Ratu, Kecamatan wonosobo. Pemilihan peserta difokuskan pada keluarga yang memiliki anak balita atau berisiko mengalami kekurangan gizi. Intervensi dilakukan melalui penyuluhan, pelatihan, dan pendampingan. Hasil: Pelaksanaan menunjukkan peningkatan pengetahuan peserra dari 89.5% berada dalam kategori baik pada pre-test menjadi 100% pada post-test. Metode ceramah interaktif, diskusi, dan praktik langsung terbukti efektif dalam meningkatkan pemahaman dan keterampilan masyarakat. Simpulan: Program BUNZIKA SEHAT berhasil meningkatkan pengetahuan dan keterampilan masyrakat dalam pemanfaatan pekarangan rumah, mendorong ketahanan pangan keluarga, dan dapat dijadikan model pemberdayaan masyarakat untuk pencegahan stunting secara berkelanjutan. Saran: Program BUNZIKA SEHAT dapat dijadikan model pemberdayaan masyarakat untuk wilayah yang lebih luas dan dapat berjalan secara berkelanjutan. Pemerintah pekon juga diharapkan memberikan dukungan melalui penyediaan bibit, pupuk, serta pendampingan rutin sehingga keberlanjutan program lebih terjamin.